Implementasi Surat Edaran Direktur Jenderal Bimbingan Masyarakat Islam Nomor P-005/DJ.III/HK.00.7/10/2021 Tentang Pernikahan Dalam masa Iddah Istri Perspektif Maslahah Mursalah (Studi di KUA Kecamatan Lubuk Pinang dan KUA Kecamatan Penarik Kabupaten Mukomuko) - Irawan, Peri; Suryani, Suryani; Zurifah, Zurifah (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The aim of this research is: First, to analyze the implementation of the Circular Letter of the Director General of Islamic Community Guidance Number P-005/Dj.III/Hk.00.7/10/2021 of the Lubuk Pinang Religious Affairs Office and the Puller Religious Affairs Office, Mukomuko Regency. Second, analyze the implementation of the Circular Letter of the Director General of Islamic Community Guidance Number P-005/Dj.III/Hk.00.7/10/2021 at the Lubuk Pinang Religious Affairs Office and the Penarik District Religious Affairs Office Maslahah Murlah Perspective. This type of research is qualitative descriptive research. This research concludes that: first, the Lubuk Pinang District Religious Affairs Office and the Penarik District Religious Affairs Office continue to provide dispensations on the condition that men who wish to marry make a stamped statement not to refer to their ex-wife during the iddah period witnessed by the family. Circular Letter of the Director General of Islamic Community Guidance Number P-005/Dj.III/Hk.00.7/10/2021 in Lubuk Pinang District and Penarik District cannot be implemented optimally because it does not have binding legal sanctions if the husband remains married. Second, in the case that occurred in Lubuk Pinang District and Penarik District, if this regulation by the Director General of Islamic Community Guidance creates harm for the household and personal life of a husband who wants to remarry but has to wait for the ex-wife's iddah period to end, it can be ignored. In other words, the benefit of remarrying during the wife's iddah period is prioritized to prevent the harm if she waits for the wife's iddah period to finish in order to prevent the man from falling into adultery because his desire to remarry is suppressed. Keywords: marriage, iddah